GE_GERICHTE P/20329/2019 vom 24. März 2022 - GE Cour de justice (2022)
ORDONNANCE PÉNALE;OPPOSITION(PROCÉDURE);PRINCIPE DE LA BONNE FOI;MINISTÈRE PUBLIC | CP.66abis; CP.66A.al2; CPP.355; CPP.391.al2; CPP.3.al2